2010
DOI: 10.20870/ijvr.2010.9.2.2772
|View full text |Cite
|
Sign up to set email alerts
|

PEGASE: A Generic and Adaptable Intelligent System for Virtual Reality Learning Environments

Abstract: The context of this research is the creation of human learning environments using virtual reality. We propose the integration of a generic and adaptable intelligent tutoring system (Pegase) into a virtual environment. The aim of this environment is to instruct the learner, and to assist the instructor. The proposed system is created using a multi-agent system. This system emits a set of knowledge (actions carried out by the learner, knowledge about the �eld, etc.) which Pegase uses to make informed decisions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…We intend to measure the expressiveness of our representation, and assess the proportion of the situations likely to be imagined by a trainer that can be modeled. Among these scenarios, we will have a particular interest in the description of collaborative tasks like in (Panzoli et al, 2014) or (Buche et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We intend to measure the expressiveness of our representation, and assess the proportion of the situations likely to be imagined by a trainer that can be modeled. Among these scenarios, we will have a particular interest in the description of collaborative tasks like in (Panzoli et al, 2014) or (Buche et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Unified Modeling Language (UML) class and state diagrams are used in (Tang and Hanneghan, 2008). (Buche et al, 2010) designs procedures in a virtual world using UML activity diagrams. (Panzoli et al, 2014) uses the Business Process Model and Notation (BPMN) language to model the activities and the interactions of several actors in a 3D virtual operating room.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Le Corre & al [18] a pedagogical scenario in the VRLEs allows to organize the training for a pedagogical purpose, however the scenario is designed for any learner without considering the individualities, which can slow learning. These authors [18] identified some weaknesses of the Intelligent Tutorial System (ITS) PEGASE for learning with virtual reality [19] and identified its lack of connection with the pedagogical scenario, its lack of modularity and its lack of individualization. To fill these weaknesses, they proposed an ITS called CHRYSAOR based on POSEIDON.…”
Section: Vrles Learning Scenario Modelsmentioning
confidence: 99%
“…However, in contrast to reflection, transformation produces a coherent content representation that consists of content elements with properties set, which enables its presentation [FW14b, FW14c]. Transformation is often performed without the use of semantic web ontologies, for example, [BQLC03, BBQC10, CTB*12, DTBRS03]. In such cases, transformation is not a part of semantic modelling, however, it is undeniably a part of a broader modelling process.…”
Section: Ontology‐based Modelling Of 3d Contentmentioning
confidence: 99%